Role of exercise and tools used in physical activities with the elderly - Szyszka, Dorota; Majewska, Małgorzata; Pietrzykowska, Barbara; Adamczyk, Jan (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
In recent years there has been an increased interest in forms of activities among older people.Regular physical exercise performed by seniors slow down the aging process, extend the period of physical and mental fitness. Regular physical activity is one way to counteract adverse processes of involution.To prevent involution situations, gymnastic, movement, dance, athletics, swimming, or related to other sports exercise can be used.The study shows the importance of some forms of physical activities for people in old age, and presented examples of exercises and tools used in physical activities with the elderly.